P523 Urethral microbiota in idiopathic Non-Gonococcal Urethritis (NGU) in men who have sex with men and men who have sex with women. (14th July 2019) - Srinivasan, Sujatha; Chambers, Laura; Tapia, Ken; Hoffman, Noah; Munch, Matthew; Morgan, Jennifer; Domogala, Daniel; Lowens, M; Proll, Sean; Huang, M; Jerome, Keith; Golden, Matthew; et al.
Abstract : Background: NGU is common with no known etiology in ∼50% of cases. We evaluated the association of urethral bacteria with NGU among men who have sex with men (MSM) and men who have sex with women (MSW). Methods: Urine samples were collected from MSM and MSW attending a Seattle STD Clinic and enrolled in a cross-sectional study. Chlamydia trachomatis (CT) and Mycoplasma genitalium (MG) were detected by TMA (Aptima), and adenovirus, HSV-1 and HSV-2 by PCR. NGU was defined as having urethral symptoms or visible discharge and ≥5 PMNs/high powered field (HPF). Absence of CT, MG, adenovirus, and HSV was considered as idiopathic NGU. Men without NGU had no urethral symptoms, no discharge, and <5 PMNs/HPF. Broad-range 16S rRNA gene PCR with deep sequencing was used to characterize the urethral microbiota. Compositional lasso analysis of bacterial taxa was conducted to identify associations between bacteria and NGU; beta coefficients (β) giving change in probability of NGU per log2 change in relative abundance are reported. Results: Of 434 (199 MSM, 235 MSW) urine samples, 330 yielded sequence data. NGU+ men were less likely to yield sequence data (70% vs 84%, Fisher's p=0.001). Of 328 men with ≥1000 sequence reads/sample, 95 MSM (44 NGU+) and 143 MSW (46 NGU+) were negative for CT, MG, adenovirus, and HSV. Higher relative abundances of Haemophilus influenzae (β=0.0139) and Mycoplasma penetrans (β=0.0095) were positively associated with idiopathic NGU in MSM, while H. influenzae was positively associated with idiopathic NGU in MSW (β=0.0184). The model also identified bacterial species that were negatively associated with NGU in MSM and MSW. Notably, Lactobacillus iners was negatively associated with idiopathic NGU in MSW (β=−0.0006) but not MSM. Conclusion: Different bacterial species are associated with NGU in MSM and MSW. We identified two bacterial species infrequently detected in the male urethra as positively associated with NGU. Disclosure: No significant relationships.